Personal archives and transitional justice in Colombia : the Fonds of Fabiola Lalinde and Mario Agudelo (2020)
ABSTRACT: This article studies two personal human rights archives and their interactions with transitional justice mechanisms in Colombia. The ‘Fabiola Lalinde fonds’ contains documentation produced during the search of truth and justice for the forced disappearance of her son Luis Fernando Lalinde. The ‘Mario Agudelo Fonds’ gathers documentation related to his militancy in the Popular Liberation Army (EPL), his later political activism and his participation in peace processes. The relationship between these archives and transitional justice can be described as a virtuous circle. Both archives preceded and prepared the implementation of transitional justice mechanisms in Colombia and have provided evidence for trials and reparation processes. In turn, transitional institutions have enhanced the public recognition of these archives as paradigmatic examples of memory initiatives of the civil society. The article shows that these types of archives can contribute to the creation of a record of human rights violations, help consolidate collective memory and have symbolic power as testimony of lives dedicated to the defence of human rights and the search for a more just country. They belong to the canon of human rights archives and, in the current Colombian context, face political and material risks that must be addressed.